Komparasi Hubungan Terpaan Iklan di Berbagai Media Terhadap Minat Beli Produk Vivo Smartphone - Abiyyu Febi Diwangkoro; Djoko Setyabudi (Jurusan Ilmu Komunikasi, FISIP, Universitas Diponegoro, 2018)
Today producers are beginning to use social media as the field product promotion them. From various media like television, newspapers, youtube, facebook, instagram, youtube.Vivo is one of the brands which when it appears often in the media. With advertising expenditure reached rp462,4 billion have been very intents explain excellence vivo to consumers. Thus should vivo is one of a smartphone owns the most attractive to in indonesia. But the intensity of the movement vivo in advertising their products it does make vivo become a smartphone most attractive to in indonesia. The purpose of this study is to find the relationship between double-digit vivo advertising in the media interest in buying products with a smartphone. Vivo The theory used in this research is a theory a response cognitive. This is quantitative research research covered with type eksplanatori.Researchers used the technique of non probability the sampling method of to the total number of samples from 100 people with the 18-30 age of years in the city of semarang that has been exposed to advertising exposure vivo smartphone. Based on the hypothesis test conducted using kendall' s know correlation, analysis it shows that there is a relationship it on each variable. The highest correlation value is the exposure of television ads by 0.532, and advertising through the newspaper of exposure 0.622, and advertising exposure through facebook with niali of 0.525.The higher the exposure to ads, vivo the higher the interest of the people buying towards. vivo products and vice versaWith the results suggested to vivo to create ads with a variety of of messages create ads with various of messages according to the desired, segmentation in order to reach the consumer segmentation in order to have interest in buying products. smartphone vivo